Fraseologia e paremiologia nell’autismo di livello 1: Nuove prospettive per la ricerca linguistica (PHRASIS | Rivista di studi fraseologici e paremiologici, 2023)
This paper is mainly focused on the study and the use of phraseological and paremiological contents by the level 1 autistic population. Specifically, the topic is treated from two different points of view: the first part is focused on the dynamics at a receptive level and the other part is about the acquisitional process of these linguistic patterns. To build a suitable research modality there will be the use of theoretical studies, which investigate in terms of method the difficulties inherent to the idiomatic and proverbial use of the language, and the application of exclusive materials to obtain results concerning the relationship between the level 1 autistic population and the linguistic structures here investigated.
Keywords: autism, phraseology, paremiology, psycholinguistics